2017
DOI: 10.1111/trf.14213
|View full text |Cite
|
Sign up to set email alerts
|

Optimal hematocrit in an artificial microvascular network

Abstract: BACKGROUND Higher hematocrit increases oxygen carrying capacity of blood, but also increases blood viscosity, thus decreasing blood flow through the microvasculature and reducing the oxygen delivery to tissues. Therefore, an optimal value of hematocrit that maximizes tissue oxygenation must exist. STUDY DESIGN AND METHODS We used viscometry and an artificial microvascular network (AMVN) device to determine optimal hematocrit in vitro. Suspensions of fresh red blood cells (RBCs) in plasma, normal saline or a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
(184 reference statements)
3
13
0
Order By: Relevance
“…Our results suggest that changes unfold in two phases bridged by a 2‐week plateau (between Days 7 and 21) when changes in RBC deformability are not statistically significant. Previous reports of deformability impairment occurring before Day 7 or after Day 21 are partly in line with our observations . Bennett‐Guerrero et al concluded that RBC deformability measured using ektacytometry was gradually altered over the 42‐day storage period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that changes unfold in two phases bridged by a 2‐week plateau (between Days 7 and 21) when changes in RBC deformability are not statistically significant. Previous reports of deformability impairment occurring before Day 7 or after Day 21 are partly in line with our observations . Bennett‐Guerrero et al concluded that RBC deformability measured using ektacytometry was gradually altered over the 42‐day storage period.…”
Section: Discussionsupporting
confidence: 92%
“…Preliminary assays (Fig. S1, available as supporting information in the online version of this paper) has shown that the flow rate of RCC sample was inversely influenced by its Hct level, which is in line with observations in similar microfluidic systems . The RBCs settling behavior of slow initial sedimentation phase followed by fast sedimentation phase was depicted by an initial steady flow rate followed by a flow rate decreases.…”
Section: Discussionsupporting
confidence: 85%
“…41 We have previously calculated theoretical oxygen transport effectiveness to assess optimal Hct values viscometrically and with the AMVN device. 42 In the present study, estimated oxygen transport effectiveness was highest at a Hct feeding of approximately 60% in all capillary microchannels studied ( Figure 6). The oxygen transport effectiveness decreased by approximately 50% in all microchannels when the differential ΔP was reduced from 60 to 5 cm H 2 O (Figure 7).…”
Section: Discussionsupporting
confidence: 51%
“…RBC transfusion in patients with anemia in whom compensatory mechanisms for adequate tissue oxygenation are reduced increases the capacity for oxygen transport [18]. A well-compensated anemia resulting from iron deficiency is the most common form of anemia and is not an indication for RBC administration itself, but as such requires the administration of iron via oral or intravenous route, with or without erythropoietin and with an assessment of the risk of adverse reactions [19].…”
Section: Discussionmentioning
confidence: 99%